Hubungan antara Kecerdasan Emosi dengan Penyesuaian Diri Mahasiswa Perantau Asal Lampung - Karmiana, Novia; , Taufik,M.Si, Ph.D (2016)
Wandering is a social phenomenon that has wide impacts. This phenomenon has been existed since the past till now. One of the supporting factors for someone to wander is to obtain a qualified education. Self-adaptation is one of problems faced by the new comer university students. To be able to do a good self- adaptation in the wandering place, emotional quotient is one of factors needed to face a new environment which is different from the previous one. This research aimed at knowing the correlation between the emotional quotient and the self-adaptation in the new comer university students from Lampung. Subjects of this research were new comer male and female students from Lampung aged 18-25 years old. The technique of sampling used cluster random sampling. The method of data collection used the scales of emotional quotient and self-adaptation. The technique of data analysis used product moment correlation. Based on the analysis of product moment, it was obtained the coefficient of correlation rxy = 0.461 and Significance (p) = 0.000; (p < 0.01). It showed that there was a positively significant correlation between the emotional quotient and the self-adaptation. The effective contribution of the emotional quotient on the self-adaptation was as much as 21.2%, that meant that 78.8% was influenced by other variables that influenced the self-adaptation except the variable of emotional quotient. The emotional quotient in the research subjects was categorize as moderate that showed by the empirical mean as much as 98.74, meanwhile, the hypothetical mean was as much as 87.5 and the self-adaptation in the research subjects was categorized as moderate that showed by the empirical mean as much as 90.49, meanwhile, the hypothetical mean was as much as 77.5.